PELATIHAN PEMBUATAN E-BOOK MELALUI APLIKASI POWER POINT DAN ANYFLIP BAGI GURU SEKOLAH DASAR - Arnidha, Yunni; Rinda Adi Puspito, Dhimas (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The reason behind this community service is that there are several obstacles in the learning process, such as a lack of students' interest in participating in the learning process and the media used being less interesting or too ordinary. The learning process is not optimal, so some students get results below the minimum completeness criteria (KKM). Learning outcomes are influenced by several factors, one of which is the role in conveying lesson material; a person needs learning media to support the information they convey, be it visual or audio-visual media. The development of these media was carried out to make the subject matter in the learning process easy for students to understand. To help increase students' interest and motivation to learn, the author tried to create an e-book using the PowerPoint and Anyflip applications. The author uses the e-book learning media development method by utilizing the PowerPoint and Anyflip applications, where through the Anyflip application, teachers are taught to develop PowerPoint material into e-books so that learning activities can provide new experiences for students and can increase participants' interest and learning outcomes in mathematics educate.